Health and Nutrition Analysis in Older Adults in San José de Minas Rural Parish in Quito, Ecuador - Roberto Ordoñez-Araque; Carla Caicedo-Jaramillo; Meybol Gessa-Gálvez; José Proaño-Zavala (Global Health, Epidemiology and Genomics)
Knowing the health and nutritional status of older adults is crucial to helping them live healthier lives and limiting the need for pharmaceuticals and complicated medical procedures. The objective of this research was to analyze the eating habits (EH), physical activity (PA), and sleep quality (SQ) of older adults in the rural parish of San José de Minas in Quito, Ecuador. Three validated questionnaires were used: the Pittsburgh PSQI for SQ, IPAQ for PA, and frequency of consumption for EH. The results revealed high consumption of refined flours and sugar (70% at least once a day), low intake of whole grains, fish, and olive oil, and considerable consumption of fruits and water. Fifty percent of respondents engage in moderate physical activity and 24% in low physical activity, while 90% of older adults have poor sleep quality. These results indicate a problem in the integral health of the population that does not allow older adults to have a good old age. Health campaigns should be developed to increase physical activity, encourage a better diet, and thus, improve the quality of sleep.